PENERAPAN METODE PENYUSUTAN AKTIVA TETAP PADA DINAS PERTANIAN KABUPATEN GARUT - Dida Farida Latipatul Hamdah; Finisa Pratama (Universitas Merdeka Madiun, 2023)
This study aims to find out how the fixed asset depreciation method is implemented in the Garut Regency Agriculture Office. Every company, including SKPD, has fixed assets for operational activities. Therefore, fixed assets have a significant role in the continuity of SKPD activities. To support each activity, SKPD will utilize the assets owned; therefore, it requires a large enough capital and has an extended period. The research method used is a descriptive analysis method, carried out by directly reviewing the research object, collecting, compiling, processing, and analyzing the data obtained. Based on the results of the study, 1) The determination of acquisition costs is appropriate because it is assessed at cost, 2) The estimated useful life of the Garut Regency Agriculture Office is under tax rules, 3) In determining the residual value or residual value, the Garut Regency Agriculture Office determines that all fixed assets owned by SKPD do not have residual value at the end of their useful life; in other words, all remaining fixed assets have the same value as zero. This study can be concluded that the application of the fixed asset depreciation method at the Garut Regency Agriculture Office needs to be revised; this is shown because the assessment does not determine the residual value. Suppose the depreciation calculation does not determine the residual value. In that case, this is less effective because it will cause the depreciation cost to be calculated too high, affecting the acquisition.